PENINGKATAN JALAN PROYEK PRESERVASI JALAN SUMUR-CIBALIUNG-MUARA BINUANGEUN - Hasiholan Silitonga, Prandi (Penerbit Lafadz Jaya, 2026)
Road preservation is crucial for regional development in Pandeglang Regency, where the 32 km Sumur-Cibaliung-Muara Binuangeun road suffers severe deterioration including cracks, potholes, and poor drainage. This study aims to analyze current road conditions, identify effective preservation methods, and design overlay and widening solutions using Manual Desain Perkerasan 2017. Employing descriptive-applicative quantitative approach in civil engineering, the population covers the entire 32 km route while sampling focuses on 2 km segment. Instruments include Dynamic Cone Penetrometer for CBR testing (32.20), traffic survey counters, and geometric measurement tools. Data analysis applies ESAL fourth power law, regional factors FR, 90% reliability, and surface indices IPo/IPt. Results yield structural overlay AC-WC 4 cm, AC-BC 6 cm, AC-Base 8 cm, Class A aggregate base 30 cm, subbase 20 cm, with road widening from 4.5 m to 7 m plus 1 m shoulders and DITCH K-350 drainage, achieving traffic capacity 2312.4 vph and saturation degree 0.59. Conclusions confirm enhanced service life and economic connectivity for agriculture and tourism.